Carbonization layer obtained by acetylene reaction with Si (100) and (111) surface using low pressure chemical vapor deposition - Hashim, Abdul Manaf (Asian Network for Scientific Information, 2008)
Surface carbonization on Si (100) and Si (111) using acetylene as single carbon source was performed in a low-pressure chemical vapor deposition chamber using rapid thermal technique. The dependence of crystallinity, crystal orientation and bonding state of carbonization layer on acetylene flow rates, pressures, temperatures and times were evaluated using X-ray diffractometry and electron probe microanalysis analytical techniques. The stoichiometric carbonization layer with good crystallinity, crystal orientation and bonding state was successfully formed at 1100°C with C2H2 flow rate of 2 sccm and reaction pressure of 0.3 Torr.